2009
DOI: 10.1017/s1463423609001091
|View full text |Cite
|
Sign up to set email alerts
|

The impact of space and time on interprofessional teamwork in Canadian primary health care settings: implications for health care reform

Abstract: Aim: This paper explores the impact of space and time on interprofessional teamwork in three primary health care centres and the implications for Canadian and other primary health care reform. Background: Primary health care reform in Canada has emphasized the creation of interprofessional teams for the delivery of collaborative patient-centred care. This involves the expansion and transformation of existing primary health care centres into interprofessional family health teams (FHT) promising to provide patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 25 publications
(39 reference statements)
6
76
0
Order By: Relevance
“…Our findings are consistent with Oandasan et al, who found that space has a substantial effect on "the quantity and quality of inter-professional communication and collaboration in primary health care." 36 We found that technology that allows for real-time communication in clinic, such as IM, was especially important in these circumstances. These issues highlight the need, particularly in large complex settings, to carefully consider how to best use space and technology to foster teamlet communication.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are consistent with Oandasan et al, who found that space has a substantial effect on "the quantity and quality of inter-professional communication and collaboration in primary health care." 36 We found that technology that allows for real-time communication in clinic, such as IM, was especially important in these circumstances. These issues highlight the need, particularly in large complex settings, to carefully consider how to best use space and technology to foster teamlet communication.…”
Section: Discussionmentioning
confidence: 94%
“…3 Increasingly, practices nationally and internationally are integrating mental health and physical services to improve quality, experience, and coordination of care for people with complex or co-occurring conditions. 9,10 However, few studies have examined how practice layout or professional proximity fosters or impairs coordination among professionals in practices integrating care. To date, research in this area suggests that merely placing professionals in the same building does not enable team-based care.…”
mentioning
confidence: 99%
“…To date, research in this area suggests that merely placing professionals in the same building does not enable team-based care. 9 Proximity of professionals working in the same location shapes professionals' feelings of isolation 10 as well as rates of engaging other professionals in patient care. 11 Therefore, the purpose of this study was to describe the observed spatial designs in 19 diverse practices integrating primary care and behavioral health and to identify how physical space and clinician proximity was connected to the behaviors of PCCs and BHCs working on these teams.…”
mentioning
confidence: 99%
“…For example, a recurring comment from participants to the ethnographer was around the perception of a physician-centeredness and hierarchy of professions within the practice. Although this was not a new finding as compared to what emerged from data collected prior to the intervention [12], the use of ethnographic methods uncovered how participants' views of physiciancenteredness and hierarchy had shifted. Informal interviews probed participants for specific examples of what physician-centeredness and hierarchy now looked like and how it affected teamwork: "Can you give me an example of a recent time when you experienced the presence of the professional hierarchy?"…”
mentioning
confidence: 80%